Violence against the Brazilian elderlies: an analysis of hospitalizations - Vivian Carla de Castro; Leidyani Karina Rissardo; Lígia Carreira
ABSTRACT Objective: to identify the prevalence of physical aggression and neglect and abandonment in the hospitalizations of Brazilian elderly people for violence and assault from 2008 to 2013 and the association of these causes with socio-demographic variables related to hospitalization. Method: quantitative, descriptive, cross-sectional study with elderlies hospitalized for assault. Inclusion criteria: to be 60 years old or over, to have been hospitalized in the Unified Health System (SUS) for assault or neglect and abandonment, between 2008 and 2013. The data were collected in February 2016, in Datasus database and descriptive and inferentially, using the Chi-square distribution, in the Epi Info 3.5.4 program. Results: the prevalence of hospitalizations due to assaults and violence prevailed among 60 and 69 years old men in the public sector. For abandonment and neglect, there was a higher prevalence in women, over 80 years old, in the public sector. Conclusion: nurses must be able to identify and prevent violence against the elderly.